Evaluation of sirtuin 1 serum level and gene expression in patients with metabolic syndrome accompanied by metabolic dysfunction-associated steatotic liver disease - Fawzy A.F. Elmessallamy; Mayada M. Mousa; Ahmad Sallam Soliman; Osama Ibrahim El-Dosoky; Samia Hussein; Basma S. Elsayed; Sara Mohamed Osama (The Egyptian Journal of Internal Medicine, 2026)
Abstract Background Metabolic syndrome is a cluster of conditions, including abdominal obesity, dyslipidemia, hypertension, and impaired glucose metabolism, that significantly increase the risk of cardiovascular disease and type 2 diabetes mellitus (T2DM). Metabolic dysfunction-associated steatotic liver disease (MASLD) was recently introduced to describe fatty liver disease linked to metabolic dysfunction. MASLD is the global primary cause of chronic liver disease nowadays. Additionally, it is a main driver of hepatic-related complications and deaths. This study was performed to evaluate serum sirtuin 1 (SIRT1) levels and gene expression in metabolic syndrome with MASLD patients and their associations with steatosis grade. Materials and methods The study participants were divided into 2 groups. Group 1 included 17 patients with metabolic syndrome with MASLD. Group 2 included 17 healthy individuals. Blood samples were collected after an overnight fast to measure fasting plasma glucose (FPG), lipid profile, and liver enzymes. Inflammatory markers (ESR and CRP) were also measured. SIRT1 serum levels were measured by enzyme-linked immunosorbent assay (ELISA). Total RNA was extracted from whole blood, and the relative SIRT1 gene expression was calculated. Results There was a significant decline in serum SIRT1 levels and gene expression with increasing grades of steatosis among metabolic syndrome with MASLD patients. Additionally, there were statistically significant positive correlations between SIRT1 gene and protein expression and HDL-C among metabolic syndrome with MASLD patients ( r = 0.60, P < 0.001 and r = 0.33, P = 0.04, respectively). Moreover, SIRT1 serum levels exhibited significant negative correlations with TG ( r =-0.30, P = 0.04) and CRP ( r =-0.35, P = 0.01). SIRT1 gene expression showed significant negative correlations with waist circumference ( r =-0.50, P = 0.004), total cholesterol ( r = -0.34, P = 0.04), and LDL-C ( r =-0.49, P = 0.004). Furthermore, receiver operating characteristic (ROC) curve analysis revealed that serum SIRT1 exhibited an accuracy of 91.2% in discriminating metabolic syndrome with MASLD with significant validity ( P < 0.001). Sensitivity was 88.2%, and specificity was 94.1%. Conclusions SIRT1 reduction at gene and protein levels is associated with the metabolic and inflammatory burden of metabolic syndrome with MASLD. The strong ROC performance of serum SIRT1 suggests its potential role as a non-invasive marker for identifying metabolic syndrome with MASLD.